Value management in the Economy 5.0 - S. L. Sazanova; L. Žák (Вестник университета)
The article considers the value management concept in the context of the changing epochs of postmodernism and metamodernism, as well as the challenges of the Economy 5.0. The main elements of the concept of value management and their relationship with the ideas of postmodernism and metamodernism have been revealed. The strengths and weaknesses of value management in modern companies have been determined. The role of institutions of the micro-, mesoand macrolevels in changing the values of economic activity has been recognized. The authors concluded that there is a cumulative, accumulative relationship between technological, value, institutional and economic changes. The potential of value management of organizations in the Economy 5.0 in the context of the era of metamodernism has been clarified.